Governing factors – surface integrity correlations and optimizations of diamond burnishing process of chromium-nickel austenitic stainless steels of the 18/8 type - Ichkova, Mariana; Anastasov, Kalin; Daskalova, Petya (International Journal of Innovative Research and Scientific Studies, 2025)
Diamond burnishing (DB), based on cold severe surface plastic deformation, is a method for modifying the surface layers of metal components in order to improve surface integrity (SI). This study aims to establish explicit correlations between the five main governing factors (burnishing force, feed rate, burnishing velocity, diamond radius, and number of passes) of DB 304 stainless steel and the main SI characteristics, including average roughness parameter Ra, shape roughness parameters skewness and kurtosis, and microhardness. DB was undertaken on a CNC lathe using flood lubrication and a one-way working scheme. A burnisher with elastic contact and a spherical-ended polycrystalline diamond insert was used. The steel, with a hardness of 250 HB, was tested in its as-received state. An experiment with a second-order composition plan, analysis of variance (ANOVA), and regression analyses was employed. The significance of the variables in the regression models was assessed using various methods to determine the influences of the governing factors and the interactions between them on the characteristics of SI. Finally, various optimizations were conducted depending on the functional purpose of the diamond-burnished surface using a non-dominated sorting genetic algorithm and QStatLab software.